(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Objective: In recent times, there have been a shift in the focus of health sector towards respectful maternity care. The concept of respectful maternity care is inclined towards client centred care with the right of women to make informed decisions concerning birth choices. The right of a woman to decide which position to adopt during childbirth has been limited the supine position in most maternity service centres and hospital settings. This study sought to investigate pregnant women’s preferred birthing positions in a tertiary health care facility in Calabar, Cross River State, Nigeria Materials and methods This study utilized the descriptive cross-sectional design to recruit 169 pregnant women using the purposive sampling techniques. The instrument for data collection was a structured and validated questionnaire. Results: Finding showed that 89.3% had good knowledge on birthing positions. Also, a good number of participants preferred the squatting position and position change as they deem comfortable during childbirth. Supine positions where the least preferred. Additionally, most participants agreed that level of education, age, previous childbirth familiarities, place of birth and support from midwives were factors that could influenced their choice of birthing positions. Conclusion: Based on these findings, the researchers recommended that midwives update their knowledge on the different birthing positions in order to educate and assist pregnant women who may desire these positions during childbirth. This will encourage the utilization of Skilled Birth Attendants (SBAs) which will help reduce maternal morbidity and mortality that would occur during childbirth on the overall.